Conversion Coefficients Measurements for 195Au - A. Gyurjinyan
The existence of Nuclear “SuperSymmetry” has been shown for the 194,195Pt, 195,196Au quartet. Nuclear SUSY allows to do structure predictions for odd-odd nucleus using excited levels of other members. The following work shows the 195Au level structure studies with internal Conversion Coefficients (ICC) measurements. ICC plays a key role on identifying excited levels, spin and polarity. In this work, conversion coefficients measurements are shown for 195Au excited levels transition. 195Pt(p,n) and 196Pt(p,2n) reactions were used to populate 195Au excited levels. The beam energy was 7.75 MeV and 12 MeV.
Keywords: Physics; Nuclear physics